2020
DOI: 10.1515/npprj-2020-0019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on filtering papermaking black liquor by dynamic blade crossflow membrane

Abstract: AbstractThe fundamental reason for the environmental pollution caused by the papermaking industry is the inadequate treatment of the black liquor. How to dispose of the lignin macromolecules, which is the main pollutants in the black liquor, is the key to addressing the environmental pollution. At present, cross-flow membrane filtration is one of the effective ways to retain and recycle lignin macromolecules in black liquor. The paper proposes the adoption of a dynamic blade cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…In diesem Zusammenhang wurde der Einsatz von keramischen tubulären Membranen beispielsweise zur Abtrennung von einigen Inhaltsstoffen aus der Schwarzlauge sowie Dünnlauge der Zellstoffproduktion untersucht [24,25,[52][53][54]. Dabei wurden keramische UF-und NF-Membranen mit verschiedenen Porengrößen als einstufiger Membranprozess bzw.…”
Section: Membranen Und Membranverfahren In Derunclassified
“…In diesem Zusammenhang wurde der Einsatz von keramischen tubulären Membranen beispielsweise zur Abtrennung von einigen Inhaltsstoffen aus der Schwarzlauge sowie Dünnlauge der Zellstoffproduktion untersucht [24,25,[52][53][54]. Dabei wurden keramische UF-und NF-Membranen mit verschiedenen Porengrößen als einstufiger Membranprozess bzw.…”
Section: Membranen Und Membranverfahren In Derunclassified
“…Wenjie Zhao et al studied the treatment of paper-making black liquor by dynamic blade cross-flow membrane filtration equipment. A membrane with a molecular weight cut-off value of nanofiltration (NP010) demonstrates the best retention effect on black liquor, and the lignin content in the treated black liquor is 28% higher than that of untreated black liquor [ 22 , 23 ]. Roger Bouzerar et al reported that the high shear force caused by disk rotation can prevent the formation of filter cake at low speed except for at the central part of the membrane [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the former, which is actually difficult to be produced in many duct flows (Guha and Frigaard 2010), crossflow existing in shear flows occurs in natural scenarios and technical applications more frequently, e.g. fluid transport at the walls of blood vessels (Majdalani et al 2002) and dewatering of pulp suspensions in paper making (Zhao et al 2020). Previous works were devoted to linear stability analysis of plane Poiseuille flow with crossflow in several ways.…”
Section: Introductionmentioning
confidence: 99%